Jim Henson's The dark crystal. Age of resistance. The quest for the Dual Glaive - Andelfinger, Nicole; Addiss, Jeffrey; Matthews, Will (Archaia, 2020)
Presents the official prequel to the series on Netflix. In the Arathim Wars, the Arathim battle the Gelfling clans of Thra. In order to save her village, the Stonewood Maudra sends Ordon, her greatest warrior, to the Tomb of Relics to retrieve a mythical weapon called the Dual Glaive. But as Ordon sets out, he soon finds that he has company; the Maudra's young daughter, Fara, has followed him. Now they must work together to get the Glaive and save their village.